Multidesign Advertising Firm / Razmee Mokhtar ... [et al.] - Mokhtar, Razmee; Abdullah, Abdul Khairi (2002)
Multidesign Advertising Firm will offer advertising and design that gives benefit to the company’s need for marketing and promotion. This company is located at Alor Setar, Kedah.